Exploring the Influence of an Interprofessional Student-Run Clinic on Matriculation to Health Professional School: A Retrospective Cross-Sectional Study - Erik Vanstrum; Sukriti Mohan; Janis Yue; Daniella Veloria; Justin Quon; Renee Lee; Kevin Knox; Cha Chi Fung (Journal of Student-Run Clinics, 2022)
Background: Projected demographic trends in the United States suggest increasing racial and ethnic diversity. It is important that the healthcare workforce reflects these trends to reduce healthcare disparities among underserved populations. For example, concordant backgrounds between patients and providers improve communication and increase probability that patients seek and receive healthcare among marginalized populations. Building in curricular opportunities to connect with the underserved community is one way to recruit students from diverse backgrounds into this pipeline that will lead to a diverse workforce in healthcare. The objective of this study was to assess the influence of an interdisciplinary student-run clinic (SRC), which focuses on caring for underserved and vulnerable populations, on students’ decisions to matriculate in four health professional programs (medical, occupational therapy, pharmacy, and physician assistant) at a single institution.Methods: In this retrospective cross-sectional survey study, we examined factors influencing first-year students’ decisions to attend a private university in a large metropolitan area. The primary outcome was students’ self-reported ratings of the university’s SRC as a factor in their matriculation decisions.  Two-tailed Mann-Whitney-U tests was applied to compare the relative importance of SRC on matriculation. Free response data were evaluated by a qualitative content approach.Results: A total of 419 students completed the survey (73% completion rate) across the 4 programs. We found that underrepresented minorities in medicine (URM) (p < 0.05) and first-generation (p < 0.01) students rated the importance of an SRC on their matriculation decision significantly higher than non-URM and non-first-generation students.Conclusions: Our findings suggest that the presence of an SRC may positively impact matriculation decisions and diversification of the student body across certain health professional disciplines.